Strategi untuk Memaksimalkan Pekerjaan Divisi Commercial pada Kantor PT Citra Maritime - Valeska Lilya Kevin; Renza Fahlevi (Jurnal Publikasi Ilmu Manajemen, 2024)
PT Citra Maritime, which is a company providing inter-island cargo transportation services, ship charter services and shipping agency services, was founded on September 12 2008 in Batam City. PT Citra Maritime has a vision to become one of the best companies in Batam City that prioritizes professional service. The implementation of this internship uses survey techniques and observations on the work that has been done and finds out what are the obstacles and causes of less effective work. From this search, things were finally found that could be changed and improved so that work could be more effective. To fill in the logbook on the SIM MBKM website, photos were obtained by documentation, while organizational structure data was obtained by interviewing PT Citra Maritime's Human Resource Development. After carrying out implementation to maximize the work of the commercial division at the PT Citra Maritime office, it is hoped that the commercial division will be helped by the implementation of this internship